2009
DOI: 10.1017/s1751731109004352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of capric acid on rumen methanogenesis and biohydrogenation of linoleic and α-linolenic acid

Abstract: Capric acid (C10:0), a medium chain fatty acid, was evaluated for its anti-methanogenic activity and its potential to modify the rumen biohydrogenation of linoleic (C18:2n-6) and a-linolenic acids (C18:3n-3). A standard dairy concentrate (0.5 g), supplemented with sunflower oil (10 mg) and linseed oil (10 mg) and increasing doses of capric acid (0, 10, 20 and 30 mg), was incubated with mixed rumen contents and buffer (1 : 4 v/v) for 24 h. The methane inhibitory effect of capric acid was more pronounced at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
31
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 27 publications
6
31
0
4
Order By: Relevance
“…In contrast, this was not observed, since the palm oil treatment reduced the fiber digestibility in a manner similar to a source rich in UFA (linseed oil). The medium-chain fatty acids such as lauric and myristic acids found in high amounts in the palm oil diets may be toxic to the bacteria and methanogenic archaea in the rumen (Soliva et al 2004a and2004b); and the dissociation of these acids in bacterial cells has been proposed as a mode of antimicrobial action (Goel et al, 2009). Manso et al (2006) also observed a negative effect on NDF digestibility with increasing level of palm oil included in diets of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this was not observed, since the palm oil treatment reduced the fiber digestibility in a manner similar to a source rich in UFA (linseed oil). The medium-chain fatty acids such as lauric and myristic acids found in high amounts in the palm oil diets may be toxic to the bacteria and methanogenic archaea in the rumen (Soliva et al 2004a and2004b); and the dissociation of these acids in bacterial cells has been proposed as a mode of antimicrobial action (Goel et al, 2009). Manso et al (2006) also observed a negative effect on NDF digestibility with increasing level of palm oil included in diets of sheep.…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial overlap between the inhibitory effects of long chain length PUFA and medium chain SFA (10:0 to 14:0) on biohydrogenation (Jenkins et al, 2008;Goel et al, 2009), methanogenesis (Martin et al, 2009) and protozoal growth (Matsumoto et al, 1991;Boeckaert et al, 2007b;Sato and Karitani, 2009). Henderson (1973) discovered, in a pure culture study, that both a Butyrivibrio spp.…”
Section: Interdependence Of Fa Biohydrogenation With Other Areas Of Rmentioning
confidence: 99%
“…and a ruminal methanogen were inhibited by 10:0 to 14:0, while other Gram-negative species were not. Comparisons in which effects of FA on both biohydrogenation and methanogenesis are measured, such as that carried out by Goel et al (2009), are rare, however. Goel et al (2009) found that capric acid (10:0) inhibited both processes.…”
Section: Interdependence Of Fa Biohydrogenation With Other Areas Of Rmentioning
confidence: 99%
See 2 more Smart Citations